The biological effectiveness of several fatty sugars in improving the growth of cut white clover seedlings Total root or vegetative transgenic bacteria Agrobacterium rhizogenes Rl601 - Najwa Khalil (مجلة التربية والعلم, 2007)
This investigation has attempted to study the effects of inoculation of removal shooting and rooting of trifolium repens seedling with Agrobacterium rhizogenes , which is resistant and sensitive to antibiotics kanamycin and cefotaxime respectively , on the number and length of branched shoots, length of root and protein content of these seedlings compared to the intact and non-inoculated seedlings as control sample In solid filed MS medium supplemented as individual or interacted with these antibiotics and lipopolysaccharide isolated from Rhizobium leguminosarum biovar trifolii, specialized to infect and formation fixed root nodules on white clover. The results have shown that the lipopolysaccharide and antibiotics cefotaxime, have improved a general effect on the protein content (22.8 and23.3 g/l),and on the mean values of the shoot length (58 and48 mm )and their branched ( 6. 8 and 7 branch/plant ), of the removal root and shoot seedlings, respectively , whereas the means of root lengths have been less than the control sample.